The Effect of Profitability, Asset Structure, Asset Growth, and Sales Growth on Capital Structure of Companies Registered at IDX Jakarta Islamic Index 2020-2022 - Putri, Negina Kencono (Proceeding International Conference on Religion, Science and Education, 2024)
The purpose of this study is to know the effect of profitability, asset structure, growth of assets, and growth of sales on capital structure at companies listed in the JII IDX for the period 2020 to 2022. This study uses a simultaneous test (F test) and a partial test (t test). Based on research and data analysis that used regression shows that profitability, asset structure, growth of assets, and growth of sales simultaneously affect the capital structure. Variable profitability, asset structure, and asset growth and sales growth partially significant positive effect on capital structure, at 10% level of significance. Adjusted R² shows a value of 0.363 indicating that 36.3% of the variable capital structure is influenced by the profitability, asset structure, growth of assets, and growth of sales. This research is expected to provide adequate information to investors who will invest their funds. In addition, it can help investors to assess company performance as reflected in the capital structure by considering profitability, asset structure and growth factors asset.